Global Phase 3 programme of vadadustat for treatment of anaemia of chronic kidney disease: rationale, study design and baseline characteristics of dialysis-dependent patients in the INNO2VATE trials. Issue 11 (14th November 2020) - Eckardt, Kai-Uwe; Agarwal, Rajiv; Farag, Youssef Mk; Jardine, Alan G; Khawaja, Zeeshan; Koury, Mark J; Luo, Wenli; Matsushita, Kunihiro; McCullough, Peter A; Parfrey, Patrick; Ross, Geoffrey; Sarnak, Mark J; et al.
Abstract: Background: Erythropoiesis-stimulating agents (ESAs) are currently the mainstay of treatment for anaemia of chronic kidney disease (CKD). Vadadustat is an investigational oral hypoxia-inducible factor prolyl-hydroxylase inhibitor that stimulates endogenous erythropoietin formation. The INNO2 VATE programme comprises two studies designed to evaluate the safety and efficacy of vadadustat versus the ESA darbepoetin alfa in ameliorating anaemia in patients with dialysis-dependent CKD (DD-CKD). Here we describe the trial design along with patient demographics and baseline characteristics. Methods: Two Phase 3, open-label, sponsor-blind, active-controlled trials enrolled adults with anaemia of CKD who recently initiated dialysis and had limited ESA exposure (incident DD-CKD trial) or were receiving maintenance dialysis with ESA treatment (prevalent DD-CKD trial). Study periods include correction/conversion (Weeks 0–23), maintenance (Weeks 24–52), long-term treatment (Weeks 53 to end of treatment) and safety follow-up. The primary safety endpoint is the time to the first major adverse cardiovascular event and the primary efficacy endpoint is the change in haemoglobin (baseline to Weeks 24–36). Results: A total of 369 and 3554 patients were randomized in the incident DD-CKD and prevalent DD-CKD trials, respectively. Demographics and baseline characteristics were similar among patients in both trials and comparable to those typically observed in DD-CKD. Conclusions: The two INNO2 VATE trials will provide important information on the safety and efficacy of a novel approach for anaemia management in a diverse DD-CKD population. Demographics and baseline characteristics of enrolled patients suggest that study results will be representative for a large proportion of the DD-CKD population.